SUPERVISION MANAGEMENT OF GOODS AND SERVICES PROCUREMENT BUREAU REGIONAL SECRETARIAT OF NORTH SUMATRA PROVINCE - Mulyono; Ahmad Sampurna; Syukur Kholil (Fakultas Ekonomi Universitas Tridinanti Palembang, 2023)
This study aims to find out how the supervisory management process in the implementation of goods/services procurement at the Regional Secretariat of North Sumatra Province is based on quality and quantity aspects as well as time aspects. This research was conducted using a descriptive method with a qualitative approach. Data collection techniques were carried out by document review and interviews. Based on the two aspects measured, namely the quality and quantity aspects and the time aspect which shows that the implementation of the procurement of goods/services at the Regional Secretariat of North Sumatra Province has been going quite well and has followed the applicable regulations. In an effort to optimize the implementation of the procurement of goods/services in the following year, the authors suggest that in terms of quality and quantity, it is hoped that there will be an increase in accelerating the process of procurement of goods/services. In the aspect of time, it is advisable to keep abreast of the development of regulations and provisions for the procurement of goods/services to maintain the quality of the results of the procurement which has been going quite well.